Comparative study of two control strategies proportional integral and fuzzy logic for the control of a doubly fed induction generator dedicated to a wind application - Chebel Ahlem; Benretem A; Dobrev I; Barkati Barkati (Institute of Advanced Engineering and Science, 2020)
This paper presents a study analysis of a complete wind energy conversion system, the system based on a doubly fed induction generator (DFIG); a vector control with stator flux orientation of the DFIG is also used to control independently the active and reactive powers. A comparative study have been performed between the conventional PI controller and fuzzy logic control to investigate its dynamic and static performances. This research work involves the study of a phase in advance, to provide effective assistance, to all those who have to make decisions regarding the planning and implementation of wind energy projects. The main objective is to model the wind chain and the use of two types of strategies for the control of this generator to ensure a good regulation we started with the modeling of the wind chain then the modeling of the DFIG and then the use of the two strategies for the regulation of the latter .The complete system is modeled and simulated in the MATLAB/ Simulink. The performance and robustness are analyzed and compared by Matlab / Simulink .Simulation results prove the excellent performance of fuzzy control unit as improving power quality and stability of wind turbine.